2016
DOI: 10.1113/jp271498
|View full text |Cite
|
Sign up to set email alerts
|

The sensory origins of human position sense

Abstract: Key pointsr Position sense at the human forearm can be measured in blindfolded subjects by matching positions of the arms or by a subject pointing to the perceived position of an unseen arm.r Effects on position sense tested were: elbow muscle conditioning with a voluntary contraction, muscle vibration, loading the arm and elbow skin stretch.r Conditioning contractions and vibration produced errors in a matching task, consistent with the action of muscle spindles as position sensors. Position errors in a point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 44 publications
(76 reference statements)
2
29
2
Order By: Relevance
“…Tsay et al . () demonstrated that conditioning of muscle spindle signals induces predictable biases in the localization of elbow joint position during limb matching but not during pointing. Although we propose that visual cues of static postural orientation are insufficient to update the balance system's representation of head‐on‐feet orientation, it is unclear if vision can play a role in transforming the direction of the vestibular‐evoked balance response under different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Tsay et al . () demonstrated that conditioning of muscle spindle signals induces predictable biases in the localization of elbow joint position during limb matching but not during pointing. Although we propose that visual cues of static postural orientation are insufficient to update the balance system's representation of head‐on‐feet orientation, it is unclear if vision can play a role in transforming the direction of the vestibular‐evoked balance response under different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Given its importance, proprioception has always received significant attention from the field of human neurophysiology (Proske & Gandevia, 2009;Tsay, Giummarra, Allen, & Proske, 2016) and, in recent years, the topic has received additional impetus owing to advances in robotic technologies that have allowed experts to develop reliable, accurate, and objective tests (Dukelow et al, 2010;Marini, Ferrantino, & Zenzeri, 2018;Marini, Squeri, Morasso, Konczak, & Masia, 2016;Rinderknecht, Popp, Lambercy, & Gassert, 2016).…”
mentioning
confidence: 99%
“…In particular, muscle spindle cues are crucial for perceiving inter‐limb orientation, but are such inputs relied upon to determine a limb's position in external space? In this issue of The Journal of Physiology , Tsay and colleagues () address this question by biasing the muscle spindle signals during an elbow joint localization task. The authors demonstrate that the use of muscle spindle cues for limb localization is context dependent.…”
mentioning
confidence: 99%